Monetary policy transmission mechanism in a small open economy under fixed exchange rate: An SVAR approach for Morocco - Rachid Ouchchikh (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2018)
Purpose: The main purpose of this study is to investigate the transmission mechanism of monetary policy in Morocco, taking external constraints on monetary policy into consideration. Design/methodology/approach: This study uses a structural vector autoregression model (SVAR) to examine the transmission of the effects of a positive monetary policy shock to the real economy. Findings: The analysis provides evidence that monetary policy shocks are transmitted to the Moroccan economy principally via credit and interest rate channels. However, the exchange rate and asset prices channels are inoperative. Furthermore, the findings show that the monetary aggregate contains important additional information in the transmission of monetary policy shocks. Research limitations/implications: Generally, the analysis leads to three policy implications. First, when analyzing the transmission mechanisms in Morocco, it is important to take into account the effect of externals shocks on monetary policy, since it allows a better appreciation of the effect and the functioning of the transmission channels. Second, since Moroccan authorities prepare its transition to an inflation targeting strategy, the functioning of the interest rate channel is important. However additional efforts are needed to develop a more resilient, competitive and dynamic financial system, to diversify the financing alternatives for the private sector, and to establish a more flexible exchange rate. Third, given the fact that the bank credit is a strong transmission channel and constitutes a major source of external financing for the Moroccan economy, it is crucial in the health and stability of the banking system as a precondition towards economic stability. Originality/value: To our knowledge, this study is the first investigation of transmission channels in Morocco using recent econometric techniques and taking into account the external constraints on monetary policy.
Keywords: C32; E52; E58; 330; Monetary Transmission Mechanisms; Structural VAR; Fixed Exchange Rate; Morocco